Upaya Peningkatan Cakupan Akseptor KB Melalui Pelatihan dan Pendampingan Kader di Kampung KB Kota Padang: Efforts to Increase Family Planning Acceptors through Training and Mentoring of Cadres in the KB Village of Padang City - Erwani, Erwani; Susanti, Dewi; Yusefni, Elda; Doni, Alsri Windra; Hayati, Neni Fitra; Ponda, Aprizal (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The incidence of unmet need family planning in Indonesia is increasing from year to year. In West Sumatra in 2017 it was 18.54%, still far from the target of reducing unmet need, total 9.91%. The high incidence of unmeet need is caused by a lack of knowledge about contraception, as well as the side effects caused by contraception. The KB village in the city of Padang has only touched 0.12% of couples of childbearing age, which is not optimal in controlling population growth. For this reason, the role of KB Village still needs to be increased through community participation and cross-sectoral integration. The aim of this econduct training and mentoring of family planning cadres in KB Village, Padang City. The method used is the participatory planning method, namely cadre training conducted 2 times pre and post test to ensure the ability of family planning cadres in implementing the program. The practical method is assisting cadres in providing education to PUS. The evaluation is carried out in two stages, namely the evaluation being carried out before the training and after the training. The final evaluation is carried out by holding meetings and evaluations with family planning cadres to find out the obstacles and follow-up plans. The result of this activity was an increase in cadre knowledge of 48.7% after training. There is an increase in the coverage of family planning acceptors in KB villages seen from the reporting of new family planning acceptors.